1998
DOI: 10.1016/s0928-8244(98)00030-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antimicrobial effect of lactoferrin on Porphyromonas gingivalis, Prevotella intermedia and Prevotella nigrescens

Abstract: The antimicrobial effect of lactoferrin (apoLf) on the oral, black-pigmented anaerobes Porphyromonas gingivalis, Prevotella intermedia and P. nitrescens has been studied. ApoLf did not kill any of these species but it did inhibit the growth of P. gingivalis, while iron-saturated Lf (FeLf) had no effect. The other two species were unaffected by apoLf. This growth inhibitory effect of apoLf could not be explained on the basis of chelation of inorganic iron, since growth of P. gingivalis occurred in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…In these investigations, it was reported that lactoferrin possessed antibacterial activities against many kinds of bacteria, such as Helicobactor pylori, Porphyromonas gingivalis, Prevotella intermedia, Prevotella nigrescens, and Staphylococcus epidermidis, as well as fungi, including C. albicans (2,60,62). In 1992, Bellamy et al (5) synthesized a potent antifungal lactoferrin peptide consisting of 25 amino acid residues, lactoferricin B, which lacked ironbinding activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these investigations, it was reported that lactoferrin possessed antibacterial activities against many kinds of bacteria, such as Helicobactor pylori, Porphyromonas gingivalis, Prevotella intermedia, Prevotella nigrescens, and Staphylococcus epidermidis, as well as fungi, including C. albicans (2,60,62). In 1992, Bellamy et al (5) synthesized a potent antifungal lactoferrin peptide consisting of 25 amino acid residues, lactoferricin B, which lacked ironbinding activity.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the antifungal activity and the pharmodynamics of peptide 2 have not yet been sufficiently explored. To establish a reasonable combined treatment of candidal infections with peptide 2 and other agents, the antifungal mechanism of peptide 2, including its influence on CDR1, CDR2, HWP1, and the enhanced filamentous growth 1 gene, which regulate candidal virulence, remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, LF has been studied for its activity against oral pathogens, including Streptococcus mutans (7), Candida albicans (38,41), and periodontopathic bacteria (2,21). Porphyromonas gingivalis and Prevetella intermedia are gram-negative black-pigmenting anaerobes that are etiologic agents of chronic adult periodontitis (26) and that reside as biofilms in the subgingival plaque (14,27).…”
mentioning
confidence: 99%
“…Porphyromonas gingivalis and Prevetella intermedia are gram-negative black-pigmenting anaerobes that are etiologic agents of chronic adult periodontitis (26) and that reside as biofilms in the subgingival plaque (14,27). hLF was shown to exhibit growth-inhibitory activity against P. gingivalis but not P. intermedia (2,35), and LFcin B was found to have weak activity against P. gingivalis (35). hLF and bLF also inhibited the adhesion of P. intermedia to epithelial cells (4).…”
mentioning
confidence: 99%
“…Lactoferrin (Lf) was first found more than 30 years ago in human maternal milk, and its antimicrobial activity was ascertained soon thereafter (1,34,41,42,45). About 10 years later, the peptides lactoferricins B and H were synthesized, along with the bovine and human Lf amino acid sequences.…”
mentioning
confidence: 99%